Nodular mucinosis of the breast: A rare entity - SALMAN, ANDAÇ; TÜRKÖZ, HÜSEYİN KEMAL; ERGUN, SAFİYE ATLAS TÜLİN; CİNEL, ZELİHA LEYLA (MARMARA UNIV, FAC MEDICINE, 2018)
Nodular mucinosis of the breast (NMB) is an uncommon disease involving the nipple-areolar region. It usually presents with asymptomatic, subcutaneous masses with indolent growth in women. Here, we report a 43-year-old man presented with a subcutaneous growth on the left nipple. Histopathological examination confirmed the diagnosis of NMB. We report our patient in order to point out this rare disease and think that the recognition of this entity is important for both clinicians and pathologists.
Keywords: Breast; Mucinosis; Nodular mucinosis of the breast